Centrosomal microtubule nucleation regulates radial migration of projection neurons independently of polarization in the developing brain - Vinopal, Stanislav; Dupraz, Sebastian; Alfadil, Eissa; Pietralla, Thorben; Bendre, Shweta; Stiess, Michael; Falk, Sven; Ortega, German Camargo; Maghelli, Nicola; Tolic, Iva M.; Smejkal, Jiri; Goetz, Magdalena; et al. (Neuron, 2023)
Cortical projection neurons polarize and form an axon while migrating radially. Even though these dynamic processes are closely interwoven, they are regulated separately-the neurons terminate their migration when reaching their destination, the cortical plate, but continue to grow their axons. Here, we show that in rodents, the centrosome distinguishes these processes. Newly developed molecular tools modulating centrosomal microtubule nucleation combined with in vivo imaging uncovered that dysregulation of centro-somal microtubule nucleation abrogated radial migration without affecting axon formation. Tightly regu-lated centrosomal microtubule nucleation was required for periodic formation of the cytoplasmic dilation at the leading process, which is essential for radial migration. The microtubule nucleating factor g-tubulin decreased at neuronal centrosomes during the migratory phase. As distinct microtubule networks drive neuronal polarization and radial migration, this provides insight into how neuronal migratory defects occur without largely affecting axonal tracts in human developmental cortical dysgeneses, caused by mutations in g-tubulin.
CRIS-Team WoS Importer:2023-05-26